Respostas

2014-04-11T19:08:28-03:00
Sendo {a=1; b=-5; c=6}
D=delta
D=b^2-4ac
D=(-5)^2-4.1.6
D=25-24
D=1

X=-b+-(raiz)D/2a
X=-(-5)+-1/2
X'=5+1/2=>X'=3
X''=5-1/2=>X''=2
2014-04-11T19:18:57-03:00
Muito fácil;
A=1
B=5
c=6

Δ= -B²-4.A.C
Δ=( -5)²-4.1.6
Δ=25-24
Δ=1

X= -B+OU- √Δ
          2.A

X= -5-OU +1=    -5-1=  -6= -3
        2.1               2        2

                            -5+1= -4 = -2
                                2      2
                          

ESPERO TER AJUDADO

Obrigada ajudou muito
de nada amo equação